Diamantina: An endemic new genus of Neotropical Atalophlebiinae (Ephemeroptera: Leptophlebiidae) evidenced by morphological and molecular data - Falcao Salles, Frederico (2020)
A new genus and species is described based on nymphs and adults collected exclusively at the Chapada Diamantina National Park, in Brazil. The generic category of this new taxon was tested by reanalyzing a morphological dataset used to access the phylogenetic relationships of species of Ulmeritus and Ulmeritoides and by the use of molecular analysis, using two different genes. Both analysis corroborated the new taxon belongs to a new genus and species, sister group of Ulmeritus-Ulmeritoides, herein described as Diamantina ulmeri gen et sp. nov. Among members of this complex, Diamantina gen nov. presents a unique apomorphy: absence of setae on lateral margins of abdominal segments. Diagnostic features include the anterior position of the proximal row of setae on dorsal surface of labrum, the U shaped emargination of labrum, eyes of male imago widely separated and shape of penis lobes.